2012
DOI: 10.1111/j.1365-2729.2012.00490.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traditional, blended and e‐learning on students' achievement in higher education

Abstract: The study investigates the effect of e‐learning, blended learning and classroom learning on students’ achievement. Two experimental groups together with a control group from Umm Al‐Qura University in Saudi Arabia were identified randomly. To assess students’ achievement in the different groups, pre‐ and post‐achievement tests were used. The results of the study (N = 148) show that there was a statistically significant difference between the three methods in terms of students’ achievement favouring the blended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
115
0
13

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(151 citation statements)
references
References 36 publications
(58 reference statements)
9
115
0
13
Order By: Relevance
“…The use of m-learning is becoming common due to many factors: new social needs in modern educational technologies, the development of market economy, improvement of the learning forms and methods (Al-Qahtani, & Higgins, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The use of m-learning is becoming common due to many factors: new social needs in modern educational technologies, the development of market economy, improvement of the learning forms and methods (Al-Qahtani, & Higgins, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Al-Qahtani and Higgins (2013) have also investigated the association between blended learning and the students' achievements during the classroom learning in Umm Al-Qura University in Saudi Arabia. The findings have shown that there was a statistically significant difference present between the implementation of blended learning processes in terms of students' achievements.…”
Section: Introductionmentioning
confidence: 99%
“…A.Y. AlQahtani et al [6] states "In the current study blended learning took the form of a combination of face-to-face classroom teaching with lecture and class formats and the use of an asynchronous online classroom". D. C. Duhaney [7] takes blended learning as a combination of the use of electronic learning tools (software, email, World Wide Web including video and/or audio streaming, television, voice mail, conference call) and traditional face-to-face classroom teaching strategies/techniques to ensure maximum effectiveness.…”
Section: Introductionmentioning
confidence: 99%